Toxoplasma Effector GRA15-Dependent Suppression of IFN-γ-Induced Antiparasitic Response in Human Neurons - Bando, Hironori; Lee, Youngae; Sakaguchi, Naoya; Pradipta, Ariel; Sakamoto, Ryoma; Tanaka, Shun; Ma, Ji Su; Sasai, Miwa; Yamamoto, Masahiro (Frontiers in Cellular and Infection Microbiology, 2019)
Toxoplasma gondii is an important human and animal pathogen that causes life-threatening toxoplasmosis. The host immune system produces interferon-γ (IFN-γ) to inhibit T. gondii proliferation. IFN-γ-inducible indole-2,3-dioxygenase 1 (IDO1), which mediates tryptophan degradation, has a major role in anti-T. gondii immune responses in various human cells. In response to the host's immune system, T. gondii secretes many virulence molecules into the host cells to suppress IFN-γ-dependent antiparasitic immune responses. The GRA15-induced proparasitic mechanism for suppressing IDO1-dependent immune responses has previously been tested only in human hepatocyte and monocyte co-cultures. Thus, whether human cells other than hepatocytes contain this virulence mechanism remains unclear. Here, we show that the GRA15-dependent virulence mechanism for suppressing the IDO1-dependent anti-T. gondii response operates in human neuronal cell lines and primary human neurons. Analysis of various human cell lines revealed that IL-1β-induced iNOS-dependent reduction of IDO1 mRNA expression occurred in brain cell lines (A172; glioblastoma, IMR-32; neuroblastoma, and T98G; glioblastoma) and liver cell lines (Huh7 and HepG2), but not in other cell lines. Moreover, co-culturing type II T. gondii-infected THP-1 human monocytes with the brain cell lines inhibited the IDO1-mediated anti-T. gondii response in a GRA15-dependent manner. These data suggest that a GRA15-dependent virulence mechanism antagonizes the IDO1-dependent host immune response in human brain cells.